Breadboard Testing of a HiPeR Inflatable Radiator (HiPeR INFRA) - Groot, T. de; Schwieters, B.; Benthem, R.C. van; Pauw, A.; Es, J. van (49th International Conference on Environmental Systems, 2019)
With a twenty times higher thermal conductivity per unit mass than aluminium, pyrolytic graphite (PG) offers great potential in the application to spacecraft thermal control systems. Over the last years, Airbus Defence and Space Netherlands (Airbus DS NL) has been developing thermal control applications for this material. The patented High Performance Radiator (HiPeR) uses the PG to efficiently spread the heat from a heat source over a large radiative area. Recently, Airbus DS NL and the Royal Netherlands Aerospace Centre (NLR) have been working on a HiPeR Inflatable Radiator (INFRA) application. This concept consists of a HiPeR radiator and a single phase fluid loop. Flexible tubing enables the radiator to be rolled up to a small stowed volume. Once in orbit, the system pressure is increased, triggering the radiator to unroll and maintain its shape over the mission lifetime. Heat is supplied via the same fluid tube that gives the radiator its shape, making use of a dedicated mini-pump. To validate the functional design, a breadboard model has been made. Deployment and thermal performance have been tested successfully. Based on the measured data, the thermal performance of an INFRA system operating at a 45 °C root temperature in a space environment with a sink temperature of -270 °C would be approximately 300-325 W/m2, corresponding to a radiator efficiency of approximately 60%. This performance is deemed to be competitive, especially considering the mass-to-power (expected <10 kg / kW after a design iteration) and small stowed volume of such a system. Additionally, a small-scale breadboard test of protection measures against micro-meteoroids and orbital debris (MMOD) has yielded promising results. The revised design includes MMOD shielding in the form of bi-stable metal strips with a resulting probability of no penetration of the kapton fluid tubing of 0,9 over a lifetime of 15 years.